Quantitative hepatitis C virus RNA and liver histology in chronic hepatitis C patients treated with interferon alfa. - Yamada, G (1993)
Seventy patients with hepatitis C virus (HCV) infection received alpha interferon at doses ranging from 3 to 10 million units (MU) daily for eight weeks, three times weekly for 12-24 weeks, or daily and three times weekly for 12-24 weeks. The efficacy of interferon was closely related to the initial blood HCV-RNA values in that these were lower in those who responded completely and partially compared with non-responders. Continuous reductions in HCV-RNA and improvements in the histology activity index score were seen in those who responded completely. In contrast, most of the partial and non-responders remained HCV-RNA positive.